Comparative Studies of Used and Fresh Lubricating Oil - Iqbal, Zafar; Akhter, Mubeen; Sabri, Muhammad Usman; Moen-Ud-Din, (European Journal of Applied Sciences, 2022)
Current research work aims to inspect the chemical analysis of engine oils as an indicator of deterioration in engines. Engine oil deterioration during long-term engine operation is a well-argued topic. This study is to investigate and compare the flashpoint, specific gravity, kinematic viscosity at 40 ⁰C &100 ⁰C, viscosity index, and sulfated ash of fresh and used engine oil of Pakistani multi grade (SAE-20W / 50, SAE- 15W / 40) and mono grade (SAE40) lubricating oil. Seventeen samples of lubricating oils were included in this investigation in which four samples are of SAE –40. The results reveal that values of flashpoint, viscosity index for oil decreased as compared to unused oil while the value of sulfated ash for oil increased as compared to unused oil.